Dissonant Works Councils and Establishment Survivability - John T. Addison; Paulino Teixeira; Philipp Grunau; Lutz Bellmann (Institute of Labor Economics (IZA), 2019)
Using subjective information provided by manager respondents on the stance taken by the works council in company decision making, this paper investigates the association between a measure of works council dissonance or disaffection and plant closings in Germany, 2006-2015. The potential effects of worker representation on plant survivability have been little examined in the firm performance literature because of inadequate information on plant closings on the one hand and having to assume homogeneity of what are undoubtedly heterogeneous worker representation agencies on the other. Our use of two datasets serves to identify failed establishments, while the critical issue of heterogeneity is tackled via manager perceptions of works council disaffection or otherwise. The heterogeneity issue is also addressed by considering the wider collective bargaining framework within which works councils are embedded, and also by allowing for works council learning. It is reported that works council dissonance is positively associated with plant closings, although this association is not found for establishments that are covered by sectoral agreements. Taken in conjunction, both findings are consistent with the literature on the mitigation of rent seeking behavior. Less consistent with the recent empirical literature, however, is the association between plant closings and dissonance over time, that is, from the point at which works council dissonance is first observed. Although the coefficient estimate for dissonance is declining with the length of the observation window, it remains stubbornly positive and highly statistically significant. Finally, there is evidence that establishments with dissonant works councils are associated with a much higher probability of transitioning from no collective bargaining to sectoral bargaining coverage over the sample period than their counterparts with more consensual works councils.
Keywords: J51; J53; J65; 330; dissonance; works councils; plant closings; collective bargaining regime; rent seeking; learning